Development and implementation of a sewing robot with artificial intelligence using the design thinking method - Mynbayev M.T. Мынбаев М.Т.; Baubekov S.D. Баубеков С.Д.; Utesheva G.T. Утешева Г.Т. (Рroblems of engineering and professional education, 2022)
This article presents the results of using the principles of the design of thinking that made it possible to create a sewing robot with artificial intelligence. The sewing robot is developed by modernizing existing sewing machines with deflected needles by using friction-transport-oriented devices for contouring parts of products.